Attention-deficit/hyperactive disorder updates - Kessi, Miriam; Duan, Haolin; Xiong, Juan; Chen, Baiyu; He, Fang; Yang, Lifen; Ma, Yanli; Bamgbade, Olumuyiwa A.; Peng, Jing; Yin, Fei (Frontiers in Molecular Neuroscience, 2022)
Background Attention-Deficit/Hyperactive Disorder (ADHD) is the neurodevelopmental disorder which commonly occurs in children with the prevalence ranging from 3.4% to 7.2%. It profoundly affects the academic achievement, well-being, and social interactions. As a result, this disorder is of high costs for both individuals and society. Despite the availability of the knowledge regarding the mechanisms of ADHD, the pathogenesis is not clear, hence, existence of many challenges especially on making correct early diagnosis and provision of the accurate management. Objectives We aimed to review the pathogenic pathways of ADHD in children. The major focus was to provide an update on the reported etiologies in humans, animal models, modulators, therapies, mechanisms, epigenetic changes, and the interaction between genetic and environmental factors. Methods References for this review were identified through systematic search in PubMed by using special keywords for all years until January 2022. Results Several genes have been reported to associate with ADHD: DRD1, DRD2, DRD4, DAT1, TPH2, HTR1A, HTR1B, SLC6A4, HTR2A, DBH, NET1, ADRA2A, ADRA2C, CHRNA4, CHRNA7, GAD1, GRM1, GRM5, GRM7, GRM8, TARBP1, ADGRL3, FGF1, MAOA, BDNF, SNAP25, STX1A, ATXN7, and SORCS2. Some of these genes have evidences both from human beings and animal models while others have evidences in either humans or animal models only. Notably, most of these animal models are knockout and do not generate the genetic alteration of the patients. Besides, some of the gene polymorphisms reported differ according to the ethnic groups. Majority of the available animal models are related to the dopaminergic pathway. Epigenetic changes including SUMOylation, methylation and acetylation have been reported in genes related to the dopaminergic pathway. Conclusions Dopaminergic pathway remains to be crucial in the pathogenesis of ADHD. It can be affected by environmental factors and other pathways. Nevertheless, it is still unclear how environmental factors relate with all neurotransmitter pathways thus, more studies are needed. Although several genes have been related to ADHD, there are few animal models studies on majority of the genes, and they do not generate the genetic alteration of the patients. More animal models and epigenetic studies are required.